Il ruolo dell’attività consultiva nell’avvio del pontificato di papa Francesco (Stato, Chiese e pluralismo confessionale, 2014)
Contributo sottoposto a valutazioneSOMMARIO: 1. Premessa - 2. Le origini della funzione consultiva nella vita della Chiesa - 3. Il Concilio Vaticano II e il rinnovato vigore della funzione consultiva - 4. Concistoro cardinalizio e Sinodo dei vescovi: esempi istituzionali dell’incidenza della funzione consultiva nella vita della Chiesa - 5. La dimensione consultiva al servizio del Successore di Pietro - 6. Conclusioni: per un “ricupero” degli elementi originali della funzione consultiva nella vita della Chiesa. AbstractThe aim of this paper is to examine the role played by the consultation principle in the life of the Church. Indeed, Pope Francesco underlined the importance of this concept and – from the beginning of his pontificate – widely used this “decision-making model”. Moreover, he based the ecclesiastical reform on this principle, in particular with the creation of the new council of cardinals, with the task to assist the holy father in the government of the Universal Church and to study possible revision of the apostolic constitution “Pastor Bonus” on the Roman Curia.Through a reflection that moves from the origins of the principle and its renewed strength during the Second Vatican Council, the paper allows concluding that the consultative principle plays a central role in the life of the church, even greater than that assumed within the jurisdiction of the states. This belief opens up further studies, able to deepen the original elements of the ecclesiastical consultation practice, with the aim of developing this model of government.